(untitled) (Journal of Bangladesh Academy of Sciences, 2015)
The purpose of this paper was to construct seven concepts of T2-space in L-topological spaces. After giving the fundamental definitions, the authors established some relations among them. Further, the authors proved that all these definitions satisfy good extension property. Finally, it is shown that these definitions are hereditary, productive and projective. Journal of Bangladesh Academy of Sciences, Vol. 39, No. 2, 203-211, 2015